Systematic laparotomy in wounds of abdomen. Analysis of 63 cases - Mintegui, Dominique; Andreoli, Gustavo; Vicente, Juan A; Keuchkerián, Marcel; Fleitas, Gabriela; Gatti, Adriana; del Campo, Juan C; Paris, Roberto (Cirugía del Uruguay, 1996)
The authors systematically performed Japarotomy in 63 abdominal wounds, 36 due to stab wounds and 25 due to tire arms, obtaining 47% and 20% of non-therapeutica/ Japarotomies in each group. Based on this and on the analysis of lesiona/ balance, re/iability of c/inica/ examination, morbility and mortality in each groups, the authors discuss the real need of a se/ective conduct, taking into account the absence of mortality and no Jow morbility in non-therapeutical laparotomies.